Understanding paraphilic self-identification: A case report and ethical considerations - Bałdyga, Paulina; Froń, Oliwia; Jurczuk, Aleksandra; Romaniuk, Sergiusz; Sołowiej, Justyna (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Sexuality in individuals with intellectual disability is often misunderstood, especially when behaviors resemble paraphilias such as pedophilia or zoophilia. Diagnostic difficulties arise from the need to distinguish true paraphilic disorders from behaviors resulting from cognitive limitations, poor judgment, and lack of sexual education. This article examines these challenges and outlines factors that may lead to pseudo-paraphilic behaviors. Material and Method: A qualitative analysis was conducted based on a case study of a 25-year-old man with moderate intellectual disability who committed sexual offenses. An interdisciplinary assessment—including psychiatric, psychological, sexological, and forensic perspectives—was used to evaluate his awareness, intent, and legal responsibility. Relevant literature was reviewed to contextualize diagnostic issues. Results: Findings show that behaviors mimicking paraphilias in this population often stem from developmental deficits, emotional tension, and limited understanding of sexuality rather than true paraphilic interest. The case illustrates the complexity of evaluating consent, motivation, and risk, as well as the difficulty in determining whether a paraphilic disorder is present. Conclusions: Assessing paraphilic behaviors in people with intellectual disability requires an individualized, holistic approach that considers cognitive, social, and educational factors. Improved sexual education and psychosocial support are essential to prevent socially inappropriate behaviors and to guide accurate clinical and legal evaluations.